Enhancing the Antibacterial Properties of Chitosan Coatings: Ag@Chitosan and Chitosan from Insects - Marsico, Michela; Azari, Rezvan; Curcio, Mariangela; Teghil, Roberto; Triunfo, Micaela; Falabella, Patrizia; Boccaccini, Aldo R.; De Bonis, Angela (Coatings, 2024)
In this study, the electrophoretic deposition (EPD) technique was used to prepare chitosan-based coatings with enhanced antibacterial activity suitable for bone implant applications. We designed, prepared, and compared the physico-chemical and biological properties of coatings obtained with commercial chitosan, chitosan enriched with silver nanoparticles, and chitosan obtained from insects. With the aim to consider the issue of sustainability, silver nanoparticles were directly prepared in the chitosan solution by laser ablation via a liquid technique, avoiding the use of chemicals and limiting the production of wastes. Moreover, a sustainable source of chitosan, such as Hermetia Illucens exuviae, was considered. The EPD process was optimized by adjusting parameters like voltage and deposition time to achieve ideal coating thickness and adhesion. The prepared films were characterized by spectroscopic and microscopic techniques such as SEM, XRD, and FTIR. Antimicrobial tests against E. coli and S. aureus revealed that silver nanoparticles enhanced the antibacterial properties of the polymer, whereas the biological evaluation using the WST8 test on MG63 human osteoblast-like cells showed that all coatings were non-toxic. Finally, chitosan obtained from insect showed comparable properties with respect to the commercial polymer, suggesting it could replace seafood-derived chitosan in biomedical applications, whereas the Ag@chitosan composite demonstrated superior antibacterial activity without compromising its biocompatibility.
CRIS-Team Scopus Importer:2024-09-06
Keywords: Ag NPs; antibacterial activity; chitosan; coating; electrophoretic deposition